Conciencia histórica : Pasado y presente en la perspectiva de los jóvenes en Portugal - Barca, Isabel (2013)
La investigación en educación histórica, de naturaleza esencialmente cualitativa en la línea de los trabajos pioneros de Peter Lee y Denis Shemilt en el Reino Unido, ha sido especialmente fructífera para una enseñanza de calidad. Actualmente, uno de sus enfoques más relevantes ha sido la prospección de indicadores de conciencia histórica de los jóvenes, en la perspectiva del filósofo Jörn Rüsen. Dentro de este marco teórico, se desarrolló un estudio con alumnos portugueses del 9° año de escolaridad con el fin de explorar, a través de las narrativas que construyen sobre la Historia del país y del mundo contemporáneo, las relaciones implícitas entre comprensión del pasado y formación de identidades a nivel nacional y global, en conexión con las concepciones acerca de cambio histórico y orientación temporal. Los resultados que se presentan son discutidos como diagnóstico de la construcción de la conciencia histórica de los jóvenes, constituyéndose como una base de reflexión para prácticas consistentes en el área de Enseñanza de la Historia
The field of research in history education developed under a qualitative tion of national and global identities, in connection with conceptions of historical change and temporal orientation. To achieve that goal, students wrote their accounts about the contemporary national and world history. The results here presented are discussed as a diagnosis of the youngsters' historical consciousness construction, providing a reflexive basis for consistent practices in the History teaching domain approach in the line of Peter Lee and Denis Shemilt pioneer work, in UK, has been especially fruitful to a consistent history teaching. One of its most relevant foci nowadays has been the inquiry about indicators of the youngsters? historical consciousness, according to the Jörn Rüsen philosophical approach. With this theoretical framework, a study wit Portuguese 9th graders was carried out to explore implicit relationships between understanding the past and the formation of national and global identities, in connection with conceptions of historical change and temporal orientation. To achieve that goal, students wrote their accounts about the contemporary national and world history. The results here presented are discussed as a diagnosis of the youngsters' historical consciousness construction, providing a reflexive basis for consistent practices in the History teaching domain
Keywords: Conciencia histórica de los jóvenes; Educación histórica; Conceptos de cambio; Orientación temporal; Historia e identidad; Youngsters' historical consciousness; History education; Concepts of change; Temporal orientation; History and identity